DDRE-02. THERAPEUTIC TARGETING OF BRAIN METASTASIS WITH ERK INHIBITOR LY3214996 USING A NOVEL IN VIVO MODEL OF LUNG-TO-BRAIN METASTASIS - Singh, Mohini (Neuro Oncol, 2020)
Brain metastases (BM) are the most common neoplasm to affect the adult central nervous system, occurring ten times more frequently than primary brain tumors. BM develop in 40–50% of advanced lung adenocarcinoma (LUAD), but the lack of durable response to chemotherapy, immunotherapy, or targeted therapy results in death within a year of BM diagnosis. Several advances have been made in identifying genetic drivers of primary cancers. For instance, the ERK pathway is critical in oncogenesis, with aberrations linked to driving the progression and metastasis of LUAD. Unfortunately, BM remain poorly understood due to both the difficulty of obtaining a sizable collection of metastatic tissue samples as well as a lack of clinically relevant models. Typical models of BM utilize inoculation routes that are invasive and cannot fully recapitulate the entirety of the metastatic cascade. Here we present a novel murine model of BM through an intrathoracic inoculation method that recapitulates the development of primary lung tumors and brain metastases as seen in patients. Using this method, we evaluated the efficacy of LY3214996, an ERK inhibitor, in targeting BM. Seven days post-inoculation of a patient-derived NSCLC-BM line, mice received LY3214996 P.O. daily for 21 days, and were monitored weekly for metastases with bioluminescent imaging. Upon endpoint lungs and brains were also removed and imaged. In vitro we demonstrated a reduction in cell growth and invasion across multiple cell lines of varying KRAS status (NSCLC and NSCLC-BM) treated with LY3214996. In vivo, we saw a reduction in both lung tumor weight as well as frequency of BM. Further research is necessary to elucidate the dosing and efficacy of LY3214996 in our models in different genetic contexts. Nonetheless, our technique presents a novel preclinical tool to interrogate the metastatic process, allowing validation of genetic drivers as well as therapeutic screening.